Ex Vivo Model to Assess the Exposure of Patients to Plasticizers from Medical Devices during Pre-CAR-T Cells’ Apheresis - Raphaëlle Lautraite; Lise Bernard; Pascale Halle; Philip Chennell; Yoann Le Basle; Justyna Kanold; Valérie Sautou (Toxics, 2022)
Background: The treatment of relapsed or refractory leukemia remains a major problem. Among the new therapeutic approaches, the use of modified T lymphocytes, called chimeric antigen receptor T cells (CAR-T cells), seems promising. The first step of their preparation is leukapheresis, which involves the collection of mononuclear cells from the patient. This medical procedure requires numerous medical devices (MDs) made of plasticized polyvinylchloride (PVC). These compounds can leach out of the devices during contact with the patient’s blood. The aim of our study was to evaluate the migration of the plasticizers contained in the MD during a simulated pre-CAR-T cell leukapheresis procedure, and to measure the patient’s and their lymphocytes’ exposure to them. Methods: The qualitative and quantitative composition of the MD used for pre-CAR-T cell apheresis was determined by gas chromatography–mass spectrometry (GC–MS). Then, an ex vivo leukapheresis model using an ethanol/water simulant was performed to evaluate the plasticizers’ migration under simulated clinical conditions of pre-CAR-T cells’ cytapheresis. The plasticizers released into the simulant were quantified by GC–MS. Results: Diethylhexylphthalate (DEHP) was found in the apheresis kit, with amounts ranging from 25% to 59% (g/100 g of PVC). Bis(2-ethylhexyl) adipate was detected at trace levels. A total of 98.90 ± 11.42 mg of DEHP was released into the simulant, corresponding to an exposure dose of 1.4 mg/kg for a 70 kg patient. Conclusions: Patients undergoing a pre-CAR-T cell apheresis are mainly exposed to DEHP, which can impact their health because of its endocrine disruption effect, but could also lead to a decrease in CAR-T cells’ efficiency/quality.